ТЕСТИРОВАНИЕ PISA. ЧТО ЭТО? - Галина Шадыбаевa; Дилбар Болтаева (INTEGRATION OF SCIENCE, EDUCATION AND PRACTICE. SCIENTIFIC-METHODICAL JOURNAL, 2021)
The article discusses the advantages of test control on the example of the international assessment of knowledge PISA